(untitled) (Research, Society and Development, 2022)
Brazil is an important tobacco exporter, while Rio Grande do Sul is the largest producer. However, tobacco growers are susceptible to various health problems during their workday, such as the Leaf Green Tobacco Disease (DFVT). Objective: To compare the hematological, hepatic and renal profile of tobacco growers with and without symptoms suggestive of DFVT in the stages of planting, harvesting and tobacco classification. Methodology: This is a case-control study using a previous database. Results: Cases of DFVT were analyzed in the stage of collection and classification, obtaining statistical significance in the dosage of monocytes during the two stages and also changes in the levels of hemoglobin during the stage of collection. Conclusion: It was concluded that tobacco growers with DFVT, during tobacco cultivation, may present changes in biochemical tests, such as monocytes and hemoglobin, thus harming their health.